The Relationship Among HRM Practices, Organizational Learning Culture, Perceived Organizational Support, Quality of Work Life, and Nurse Retention - Firanka, Safirra Afifah; Hendarman, Achmad Fajar (Jurnal Locus Penelitian dan Pengabdian, 2026)
Nurse retention is an important issue in maintaining the quality of health services and workforce sustainability in hospitals. RSUP Sardjito, as one of the national referral hospitals, plays a central role in absorbing nursing personnel in Yogyakarta. However, the high proportion of contract nurses indicates the need for more appropriate organizational strategies to improve retention. This study adopts three main theories—Social Exchange Theory, Organizational Support Theory, and Job Demand-Resources Theory—as a theoretical framework to analyze the relationship among HRM practices, organizational learning culture, perceived organizational support, quality of work life, and nurse retention. It employs a quantitative approach using multiple regression analysis based on survey data collected from nurses at RSUP Sardjito. The results are expected to contribute theoretically by integrating structural, cultural, and psychosocial approaches in explaining nursing staff retention. Practically, these findings are expected to serve as a reference for hospital management and policymakers in designing strategies that support a positive work environment, enhance commitment, and increase nurses' intention to stay in their jobs sustainably.